35.9k views
5 votes
Solve the linear systems using the substitution method. 2x-3y=-1 x=y+1

Please explain the steps too. Thank you. :)

User Bedeabza
by
6.2k points

1 Answer

4 votes

Answer:

x =1 and y=-1

Explanation:

2x - 3y=-1

x-y=1

there for ok there is a lot of steps i had to do so ill take a pic of it

and the big one is the first one

Solve the linear systems using the substitution method. 2x-3y=-1 x=y+1 Please explain-example-1
Solve the linear systems using the substitution method. 2x-3y=-1 x=y+1 Please explain-example-2
User Jigna
by
6.4k points